OPTIMAL MODE OF DOUBLE SIDED DIFFUSION IN A SILICON MONOCRYSTAL FOR NUCLEAR RADIATION DETECTORS - Saymbetov А.К; Japashov Н.М.; Nurgaliyev М.К.; Kuttybay Н.Б.; Koshkarbay Н.Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The paper is aimed at finding the optimal mode of double sided diffusion of lithium into a silicon monocrystal for the manufacturing large-size Si (Li) detectors. In this work, a numerical method was used to simulate the processes of double sided diffusion of lithium atoms into monocrystal silicon to solve the diffusion problem with boundary conditions. The MATLAB software environment was used for modeling and solving problems. The physical characteristics of dislocation-free monocrystal p-type silicon were chosen as the initial material in the simulation process. Based on the results of modeling the double sided diffusion of lithium into a silicon monocrystal the optimal mode for obtaining large-diameter Si (Li) detectors was determined. To obtain detectors with a diameter of ≥ 100 mm with thickness of a sensitive area ​​more than 4 mm, the optimal temperature is 430-450 0C for time 3 min with a lithium penetration depth hLi = 300 ± 10 μm.